2013
DOI: 10.1111/pan.12234
|View full text |Cite
|
Sign up to set email alerts
|

Washout times of desflurane, sevoflurane and isoflurane from the GE healthcare Aisys® and Avance® Carestation® and Aestiva® Anesthesia System

Abstract: This study demonstrates that saturated vapor pressure and priming concentration exert a greater effect on washout times than gas solubility. The Aisys utilizes an electronic vaporizer system that may expose the breathing system to retained saturated vapor. The breathing systems for all machines may hinder washout of gases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…Indeed, though the ECoG appears active by the end of washout in our study, prior studies have shown residual levels of isoflurane up to 10 minutes after initiation of washout (Kim and Tham, 2013; Torri et al, 2002). Thus, future studies can elucidate the potential role of residual isoflurane on neural correlates of consciousness by using other anesthetic agents, other modes of CA induction, and modification of anesthesia washout periods as permitted within the confines of approved animal protocols.…”
Section: Discussioncontrasting
confidence: 56%
“…Indeed, though the ECoG appears active by the end of washout in our study, prior studies have shown residual levels of isoflurane up to 10 minutes after initiation of washout (Kim and Tham, 2013; Torri et al, 2002). Thus, future studies can elucidate the potential role of residual isoflurane on neural correlates of consciousness by using other anesthetic agents, other modes of CA induction, and modification of anesthesia washout periods as permitted within the confines of approved animal protocols.…”
Section: Discussioncontrasting
confidence: 56%
“…The necessary procedures and decontamination times vary depending on construction and applied materials among the different manufacturers and generations of machines 6468. Maintaining a high fresh gas flow (eg, 10 L per minute) throughout the procedure seems to be important for avoiding a rebound phenomenon 6468.…”
Section: Anesthesia In Patients Predisposed To Mhmentioning
confidence: 99%
“…The necessary procedures and decontamination times vary depending on construction and applied materials among the different manufacturers and generations of machines 6468. Maintaining a high fresh gas flow (eg, 10 L per minute) throughout the procedure seems to be important for avoiding a rebound phenomenon 6468. Activated charcoal filters inserted into the breathing circuit can accelerate the purging procedure and might be valuable when preparing a machine for trigger-free anesthesia and for use in an acute MH crisis 69.…”
Section: Anesthesia In Patients Predisposed To Mhmentioning
confidence: 99%
“…Three co‐author names and funding information were erroneously omitted in the article by Kim & Tham . In addition, there is a typographical error in the title: ‘GE healthcare’ should be ‘GE Healthcare’.…”
Section: Washout Times Of Desflurane Sevoflurane and Isoflurane Frommentioning
confidence: 99%